Luffa—an Asian Vegetable Emerging in Florida - Yucong Xie; Guodong Liu; Yuncong Li; Katie Migliaccio (EDIS)
Luffa is the genus name of several tropical and subtropical plants in the cucumber family. Alternatively spelled “Loofa” or “Loofah,” the name is derived from the plant’s use as a material for sponges and dish cloths for bathing and cleaning dishes. This 6-page fact sheet describes the two types of Luffa, how to cultivate them, and what they can be used for. Written by Yucong Xie, Guodong Liu, Yuncong Li, and Kati Migliaccio, and published by the Horticultural Sciences Department, September 2016.